Unfavorable Anatomical Factors Influencing the Success of Retrograde Intrarenal Surgery for Lower Pole Renal Calculi - Kilicarslan, Hakan; Kaynak, Yurdaer; Kordan, Yakup; Kaygisiz, Onur; Coskun, Burhan; Gunseren, Kadir Omur; Kanat, Feyzi Mutlu (Urology Journal, 2015)
Purpose: To determine the unfavorable factors, related to lower pole anatomical characteristics (LPACs), influencing the success of retrograde intrarenal surgery (RIRS) for lower pole renal calculi (LPC). Materials and Methods: We reviewed the data of 36 patients who underwent RIRS for LPC between October 2012 and October 2013. The infundibulopelvic angle (IPA), infundibular length (IL) and infundibular width (IW) were measured on preoperative intravenous urographies. On follow-up stone-free status was defined as complete clearance at the first month kidney-ureter-bladder X-ray and computed tomography if necessary. Results: The median stone size was 10 mm (range, 5-35). The stone-free rates according to LPACs at the first month follow-up were 100% (n = 17), 57.9% (n = 11), 90% (n = 18), 62.5% (n = 10), 90.5% (n = 19) and 60% (n = 9) for patients with IPA ≥ 70°, IPA < 70º, IL < 3 cm, IL ≥ 3 cm, IW ≥ 5 mm and IW < 5 mm, respectively. While IPA and IW were associated with success of RIRS for LPC in multivariate analysis (P = .003 and P = .046, respectively), only IW was found to be a significant factor after applying multivariate analysis (P = .05). Conclusion: The results of our study demonstrated that only IW had a significant effect on the success rate of RIRS for LPC.